2009
DOI: 10.1242/dev.026211
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin stiffens the vertebrate embryo during crucial stages of elongation and neural tube closure

Abstract: Physical forces drive the movement of tissues within the early embryo. Classical and modern approaches have been used to infer and in rare cases measure mechanical properties and the location and magnitude of forces within embryos. Elongation of the dorsal axis is a critical event in early vertebrate development yet the mechanics of dorsal tissues in driving embryonic elongation that later support neural tube closure and formation of the central nervous system is not known. Among vertebrates, amphibian embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
250
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(277 citation statements)
references
References 63 publications
25
250
2
Order By: Relevance
“…23 In developing Xenopus embryos, a temporal and spatial distribution of mechanical stiffness directs early patterning and differentiation events, with cells creating these gradients of stiffness through actomyosin contraction. 24 Zhou and coworkers found that profound tissue stiffening occurs from the gastrula to neurula stages, and this stiffening had an impact on neural tube formation. By treating tissue explants with latrunculin B, an actin-depolymerizing drug used to reduce actomyosin contraction, the researchers were able to reduce tissue stiffness by more than 50%, suggesting that cell-mediated actomyosin contractility is responsible for much of the tissue stiffening that occurs during this stage of development.…”
Section: Cellular Response To Ecm Stiffness During Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In developing Xenopus embryos, a temporal and spatial distribution of mechanical stiffness directs early patterning and differentiation events, with cells creating these gradients of stiffness through actomyosin contraction. 24 Zhou and coworkers found that profound tissue stiffening occurs from the gastrula to neurula stages, and this stiffening had an impact on neural tube formation. By treating tissue explants with latrunculin B, an actin-depolymerizing drug used to reduce actomyosin contraction, the researchers were able to reduce tissue stiffness by more than 50%, suggesting that cell-mediated actomyosin contractility is responsible for much of the tissue stiffening that occurs during this stage of development.…”
Section: Cellular Response To Ecm Stiffness During Embryonic Developmentmentioning
confidence: 99%
“…25 Similarly, patterning of the anteroposterior axis is stabilized by the generation of actomyosin-based tension, which acts to organize and stiffen the ECM in the paraxial somatic mesoderm. 24 Tight junctions and adherens junctions mediate the forces exerted between cells to compartmentalize these developing tissues. Additionally, myosin II is enriched at sites of tension application on the surface of intercalating cells, 26 suggesting that anisotropy in the micromechanical environment contributes significantly to pattern formation.…”
Section: Cellular Response To Ecm Stiffness During Embryonic Developmentmentioning
confidence: 99%
“…Our model produces strain patterns similar to those observed in experiments. Based on previous measurements of the viscoelastic material properties of Xenopus embryos (18,19), the shear modulus ranges from 3 to 15 Pa over these stages. Our FE model shows how tissues displace beyond the area exposed to ATP.…”
Section: Significancementioning
confidence: 99%
“…S13). Such a wave velocity is sustained in Xenopus embryonic tissues rather than being immediately damped because the time constant of viscoelastic dissipation, ∼60 s, is longer than the time taken by a wave to pass through the tissue (18,19). The kinematics of these wave-like contraction responses to periodic stimulations can be understood and predictably simulated using system dynamics theory.…”
Section: Significancementioning
confidence: 99%
“…In fact, during Xenopus gastrulation, polarized morphogenetic movements are driven in a similar manner by cortical actomyosin remodeling. 48,49 Interestingly, the cytoskeletal forces from within the cells also influence signaling pathways that mediate localized assembly of extracellular matrix. 50 These results, taken together, suggest that it is possible that both the cellular and extracellular (matrix) forces/properties driving local morphogenetic movements are recruited by a common upstream signal.…”
Section: Molecular Drivers Of Local Morphogenetic Movementsmentioning
confidence: 99%